2022
DOI: 10.1371/journal.pcbi.1010142
|View full text |Cite
|
Sign up to set email alerts
|

Fluid mechanics of the zebrafish embryonic heart trabeculation

Abstract: Embryonic heart development is a mechanosensitive process, where specific fluid forces are needed for the correct development, and abnormal mechanical stimuli can lead to malformations. It is thus important to understand the nature of embryonic heart fluid forces. However, the fluid dynamical behaviour close to the embryonic endocardial surface is very sensitive to the geometry and motion dynamics of fine-scale cardiac trabecular surface structures. Here, we conducted image-based computational fluid dynamics (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…It is unclear whether tissue internal stresses played an important role as well. In our previous microscopy-based flow simulations (Cairelli et al, 2022), we found that there were widely varying fluid WSS characteristics at regions that trabeculated, and the general fluid WSS characteristics at regions that trabeculated did not differ from regions that did not. This suggested that fluid WSS may not be the only stimuli needed for trabeculation.…”
Section: Introductionmentioning
confidence: 64%
“…It is unclear whether tissue internal stresses played an important role as well. In our previous microscopy-based flow simulations (Cairelli et al, 2022), we found that there were widely varying fluid WSS characteristics at regions that trabeculated, and the general fluid WSS characteristics at regions that trabeculated did not differ from regions that did not. This suggested that fluid WSS may not be the only stimuli needed for trabeculation.…”
Section: Introductionmentioning
confidence: 64%